Successful outcome of open distal interphalangeal joint luxation in equids treated by surgical debridement without internal implants - L. C. Ferrari; E. V. P. Apolonio; S. L. de Oliveira-Gonçalves; A. L. A. Rambo; J. V. Bergamasco; J. M. Alonso; M. J. Watanabe; A. L. G. Alves (Veterinary Research Communications, 2026)
Introduction The distal interphalangeal joint (DIPJ) plays a crucial role in the function of the hoof and digit. Dislocations and subluxations in this region are rare and primarily of traumatic origin. Case Report This case report aims to describe two unusual cases of open DIPJ dislocation, including clinical presentation, diagnostic workup, treatment, and long-term follow-up. Both animals presented with open traumatic distal interphalangeal joint (DIPJ) luxation. In Case 1, the animal received initial care on the property 5 h post-trauma and presented with joint exposure and articular surface contact with the ground. In Case 2, the animal was referred to the veterinary hospital without prior care, 3 h post-trauma, but there was no contact of the articular surface with the ground. Both animals showed grade 5/5 lameness (AAEP). The animals underwent general anesthesia, joint lavage, regional intravenous perfusion with antibiotics, debridement of devitalized tissues, skin synthesis, and immobilization with synthetic casting. During immediate recovery and hospitalization, a grade 4/5 lameness persisted. Long-term radiographic control revealed the development of degenerative joint disease in both animals. After 3 and 2 years, respectively, animals 1 and 2 showed persistent lameness (grade 2/5) with an absence of local sensitivity. Conclusion The conservative treatment employed in these cases of open DIPJ luxation proved effective for the maintenance of the patients’ lives, and although the infectious pathological process invariably progressed to osteoarthritis, the evolution of the clinical conditions allowed for light exercise and maintenance of reproductive activity.